2012
DOI: 10.1017/s0266467412000491
|View full text |Cite
|
Sign up to set email alerts
|

Litter as a filter of emergence for herbaceous seedlings and sporophytes in central Amazonia

Abstract: Abstract:We conducted a study in 30 plots distributed uniformly in an area of 25 km2 at Ducke Reserve, Manaus, to test the hypothesis that understorey herb richness and abundance are mediated by litter, manipulating experimentally the amount of litter in the field. Over 10 mo, we followed the emergence of herbaceous seedlings and sporophytes in control, litter-addition and litter-exclusion treatments, covering an area of 1.2 m2 per plot in each treatment. We also assessed the relationship between topography an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Finally, both ferns and the Melastomataceae tended towards significantly steeper microsites than expected at random, whereas patterns in trees did not differ from random expectation. Similar patterns have been detected in ferns and in some other herbaceous understorey plant groups in earlier studies (Costa 2006, Jones et al 2014, Poulsen et al 2006, Rodrigues & Costa 2012). This might represent avoidance of the most poorly drained sites at lower topographic position, but it could also be related to other factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, both ferns and the Melastomataceae tended towards significantly steeper microsites than expected at random, whereas patterns in trees did not differ from random expectation. Similar patterns have been detected in ferns and in some other herbaceous understorey plant groups in earlier studies (Costa 2006, Jones et al 2014, Poulsen et al 2006, Rodrigues & Costa 2012). This might represent avoidance of the most poorly drained sites at lower topographic position, but it could also be related to other factors.…”
Section: Discussionsupporting
confidence: 87%
“…This might represent avoidance of the most poorly drained sites at lower topographic position, but it could also be related to other factors. There is, for example, evidence that the establishment success of small-seeded plant species and spore-producing ferns is negatively related to leaf litter depth, and litter accumulation is likely to be lower on slopes relative to flat sites (Metcalfe et al 1998, Molofsky & Augspurger 1992, Rodrigues & Costa 2012). Metcalfe & Grubb (1995) found a general tendency for seed size to be related to adult plant stature in shade-tolerant rain-forest plants, being smaller on average in shrubs and herbs than in trees.…”
Section: Discussionmentioning
confidence: 99%
“…A preference for slope habitats by herbs has also been found in a few earlier studies (Poulsen ; Costa ). In Amazonia, this has been found to be related to lower litter accumulation on slopes (Rodrigues & Costa ). Sloping sites may also provide more favourable drainage conditions, especially at lower landscape positions where there may be periodic waterlogging.…”
Section: Discussionmentioning
confidence: 96%
“…This may explain the wide geographical distributions of many fern species (Smith ; Tryon ). On the other hand, because of their gametophytic life stage, ferns are more sensitive than seed plants to being covered by leaf litter (Rodrigues & Costa ).…”
Section: Introductionmentioning
confidence: 99%
“…Th is might have a strong impact on the emergence of certain plant species that require shallow or no litter layers to establish (Costa 2006). For example, in a recent study in central Amazonia, Rodrigues and Costa (2012) found that pteridophyte and monocot emergence was 2 -4 times higher in plots with all litter removed than in plots with a relatively deep litter layer. In temperate beech forests in Denmark species such as Hepatica nobilis Mill.…”
Section: Biotic Effectsmentioning
confidence: 99%